Defect of Modern Development: An Analysis of Destroying Traditional Chautaris - Panta, Saroj Raj (International Research Journal of MMC, 2025)
This paper examines the destruction of Chautari in Phalebas Municipality-7, Limithana, Parbat, using a survey research design and purposive sampling. The study found that modern development activities are responsible for the decline of Chautaris, with most respondents citing the destruction of trees and the use of AC and fans instead of Chautari. The study also found that Bar, Peepal, and Sami trees play a crucial role in controlling harmful insects. The decline of Chautaris is attributed to migration, the decline of native traditional culture, the rise of modern transportation, and political influences. The lack of traditional rituals and the dominance of modern transportation contribute to the erosion of cultural continuity. The study emphasises the importance of preserving Chautaris to maintain the region's cultural heritage and highlights the need for strong collaboration among stakeholders, including academia, researchers, and planners. The findings will be beneficial for academia, researchers, and planners in addressing these issues and preserving the region's cultural heritage.